Acceptability of Toddlers to Preparations Made From Toddler Supplementary Feeding Biscuits and Pumpkin as an Supplementary Feeding Extension - Mirthasari Palupi; Theresia Puspita (Journal of Global Research in Public Health, 2025)
Pumpkin or Cucurbita moschata is one of the plants food sources that have high nutritional and fine fiber so that it is easily digested. The use of pumpkin mixture with supplementary feeding toddler biscuits will increase the nutritional value of supplementary feeding toddlers because pumpkin meat has a rich content of vitamins A, B and C, minerals, and carbohydrates. In this study, pumpkin and supplementary feeding biscuits were processed into steamed cake, cookies, and pudding with the aim of knowing the acceptability and food waste of steamed cake, cookies, and pudding. This research was conducted at the Taman Posyandu Melati Dawuhan Kidul Village, Papar District, Kediri Regency. The data collection technique of this study used the residual food acceptance test (Comstok) with descriptive analysis method and with quasi-experimental method conducted on 23 randomly selected respondents with the criteria of toddlers aged 3-5 years and are members of taman posyandu Melati who are not allergic to food ingredients. Based on the acceptability test of the remaining steamed cake food with 0% residue as much as 60%, cookies remaining 0% as much as 43.40%, pudding remaining 0% as much as 13%. Acceptability test of food waste with 0% food waste is steamed cake as much as 60%. It is recommended that for cookies products, the texture is less dry, the addition of pumpkin is reduced. The pudding is too mushy, so the ratio of agar flour is still lacking. The purpose of this study was to determine the acceptability of the remaining steamed cake, cookies, and pudding. Using of local and affordable food is necessary for the health of toddlers